Stability of multiple dynamic nonlinear systems - (:unkn) unknown (I E E E, 1997)
Stability of Multiple Dynamic Systems (time varying, discrete or continuous time systems with dynamics which are chosen from a given finite set) are considered. Such systems are governed by a finite set of dynamics according to some rule. Some stability definitions and stability measures are provided for general kind of nonlinear multiple dynamic systems. Similar to linear multiple dynamic case many results are obtained and generalized for nonlinear multiple dynamic systems.